Efficacy of budesonide/formoterol and tiotropium combination for the treatment of Chinese patients with chronic obstructive pulmonary disease. Issue 22 (June 2018) - Feng, Jun-fei; Ding, Guo-rong; Xie, Yan-zhong; Zhao, Dejun; Wang, Xuehui
Abstract : Abstract: This study investigated the efficacy and safety of budesonide/formoterol (B/F) and tiotropium combination in the management of chronic obstructive pulmonary disease (COPD) in Chinese patients. Between January 2015 and November 2017, 113 eligible Chinese patients with COPD were included and divided into an intervention group and a control group. Sixty-three patients in the intervention group underwent B/F combined tiotropium, while 50 patients in the control group received tiotropium alone. The primary outcome was severity of dyspnea on exertion (DOE), measured by the 6-minute walk test (6MWT) scale. The secondary outcomes included lung function, measured by the forced expiratory volume in 1 second (FEV1 ), quality of life, measured by the St. George's Respiratory Questionnaire (SGRQ), and adverse events. All outcomes were measured at the end of 12-week treatment. B/F and tiotropium combination showed greater efficacy in DOE ( P  < .01), lung function ( P  < .01), and quality of life ( P  < .01), compared with tiotropium alone at the end of 12-week treatment. In addition, adverse events in both groups were similar and tolerable. The findings suggest that B/F and tiotropium combination can be used as an effective treatment in Chinese patients with COPD.